Urgensi Izin Keamanan Pangan (P-IRT) dalam Upaya Membangun Kepercayaan Konsumen dan Meningkatkan Jaringan Pemasaran - Majdi, Ahmad Labib; Farhani, Julita; Wulansari, Rena; Dari, Nur Oktriani Wulan; Fuadah, Alit Latifatul; Haqq, Munadhil Izzul; Falahudin, Adam Muhammad; Khotimah, Ai Lia; Budi, Kasih Ariefta; Aziz, Busrol; Febriyani, Nurlinda; Assyifa, Jasmine (Lembaga Pengabdian kepada Masyarakat (LPkM) Universitas Islam Darussalam (UID) | Islamic University of Darussalam Ciamis-Jawa Barat, 2024)
This study discusses the importance of Food Safety Permit or Home Industry Food (P-IRT) for micro, small, and medium enterprises (MSMEs) in the food sector. The purpose of this study is to analyze the role of P-IRT certificates in building consumer trust and expanding food product marketing networks. In this study, researchers used the Participatory Action Research (PAR) method with primary and secondary data sources, namely through observation, interviews, and literature studies. The results of the study indicate that P-IRT is not only a legal obligation, but also plays a strategic role in increasing consumer trust, opening wider market access, and increasing product competitiveness. The implication of this study is the importance of awareness and compliance of MSME food actors to obtain P-IRT as part of a sustainable business development strategy.